2011
DOI: 10.1016/j.anbehav.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of innovation and sex-specific migration on neutral cultural differentiation

Abstract: Keywords cultural trait population structure sex-biased migration sex-biased social learning Studies of behaviour are increasingly focusing on acquisition of traits through cultural inheritance. Comparison of patterns of spatial population structure (F ST ) between neutral genetic loci and behavioural or cultural traits can been used to test hypotheses about demography, life history, and the mechanisms of inheritance/transmission of these traits in humans, chimpanzees and other animals. Here, we develop analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
3
4
0
Order By: Relevance
“…Tool use is a very convenient indicator for local traditions but it is restricted to relatively few primate species, while our approach could be used more generally. Our results are in line with predictions of a model that takes sex-biased dispersal into consideration (Yeaman et al 2011). On the other hand, neighbouring chimpanzee groups may differ with respect to socially learned behaviour (Boesch 2003).…”
Section: Further Methodological Considerationssupporting
confidence: 90%
See 2 more Smart Citations
“…Tool use is a very convenient indicator for local traditions but it is restricted to relatively few primate species, while our approach could be used more generally. Our results are in line with predictions of a model that takes sex-biased dispersal into consideration (Yeaman et al 2011). On the other hand, neighbouring chimpanzee groups may differ with respect to socially learned behaviour (Boesch 2003).…”
Section: Further Methodological Considerationssupporting
confidence: 90%
“…An expansion of chimpanzee study groups at Ta€ ı National Park, Ivory Coast, demonstrates the pitfalls of small sample size: a tool-use behaviour previously classified as a tradition in the population was present only in the first but not in the second study group (Boesch 2003). These data are in line with a recent model that proposes that different traditions may arise not only between distant populations of the same species but also on a more local scale and even between neighbouring groups (Yeaman et al 2011). Such group-level traditions are particularly likely to occur if two conditions are met, and which apply to our study species, the vervet monkey.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, the likelihood that immigrants enter communities at a low point in the social hierarchy (Kahlenberg et al, 2008), provides an alternative, or additional, explanation to conformity to group traditions (Haun et al, 2012; Luncz & Boesch, 2014; Luncz et al, 2012), for the observation that cultural repertoires of neighboring chimpanzee communities may differ despite shared knowledgeable migrants (Biro et al, 2006; Luncz et al, 2012; Luncz & Boesch, 2014, but see Lind & Lindenfors, 2010; Nunn, Thrall, Bartz, Dasgupta, & Boesch, 2009). Indeed, these findings echo those of Yeaman, Bshary, and Lehmann (2011) who, in an analytical model, found that opposite biases in individuals who are learned from, and individuals who migrate, resulted in high cultural trait variation among groups relative to a genetic model. However, the consistency of our data with chimpanzees employing a “copy knowledgeable individuals” strategy complicates this interpretation; females display their alternative behavioral traits for some time following immigration (Luncz & Boesch, 2014) and thus low-ranked immigrants may still be copied if they exhibit cues of proficiency with new skills.…”
Section: Resultssupporting
confidence: 72%
“…Yeaman et al . [22] modelled social learning rules in combination with migration patterns and found that the interaction produces conditions in which traditions may form on the population level and conditions under which traditions may form on the group level or within even smaller units. Observations on foraging technique development suggest that in several wild primate species, mothers are central for technique acquisition [23] [27] .…”
Section: Introductionmentioning
confidence: 99%